Application of Lubrication into the Hip Joint Replacement - Haringová, Andrea; Stračár, Karol; Prikkel, Karol (Manufacturing Technology Journal, 2016)
The article deals with application of knowledge from lubrication of healthy spherical joints into hip joint endoprosthesis. As the observed most important physical parameter it was selected the coefficient of friction responsible directly for lifetime of the endoprosthesis. The article describes as well as experimentally verifies the idea of additional lubrication of hip joint endoprosthesis.
Keywords: lubrication; coefficient of friction; endoprosthesis